2000
DOI: 10.1152/ajpheart.2000.279.4.h1441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exercise on calcium signaling in rat vascular endothelium

Abstract: Chronic exercise enhances endothelium-dependent vasodilating responses. To investigate whether this is due to a change in endothelial Ca(2+) signaling, we examined intracellular Ca(2+) concentration ([Ca(2+)](i)) level in rat aortic endothelium in response to acetylcholine (ACh) or ATP. Four-week-old male Wistar rats were divided into control and exercise groups. The exercised animals ran on a treadmill at a moderate intensity for 60 min/day, 5 day/wk, for 10 wk. Rat aortas were then excised and loaded with fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002. This data along with our previous data on UAEC led us to believe that the sustained phase of the [Ca 2C ] i response in NP-UAEC is relatively unresponsive, while P-UAEC mobilize Ca 2C more like calf pulmonary artery EC, bovine aortic EC, and rat aortic EC (Chu et al 2000, Bishara et al 2002, Wilkinson & Jacob 2003.…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002. This data along with our previous data on UAEC led us to believe that the sustained phase of the [Ca 2C ] i response in NP-UAEC is relatively unresponsive, while P-UAEC mobilize Ca 2C more like calf pulmonary artery EC, bovine aortic EC, and rat aortic EC (Chu et al 2000, Bishara et al 2002, Wilkinson & Jacob 2003.…”
Section: Introductionsupporting
confidence: 58%
“…Thus, although acute exercise increased the vascular responses to endothelium-dependent vasodilators (such as ACh), data points from the exercise group only extended to high levels of EC [Ca 2ϩ ] i elevations that accompanied a little additional vasorelaxation. In separate studies, we found that chronic exercise enhances ACh-induced vasorelaxation (4,6) and the EC [Ca 2ϩ ] i response (9). Perhaps the chronic exercise also affects vasorelaxation by altering EC [Ca 2ϩ ] i signaling.…”
Section: Comparison Of Ach-induced Calcium Responses and Vasorelaxatimentioning
confidence: 90%
“…The basic setup for EC [Ca 2ϩ ]i imaging was similar to that described in our previous reports (9,13). Fura 2-loaded vessel rings were opened longitudinally and pinned to the base plate of a tissue flow chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the exercise-induced changes are likely due to local increases in blood flow or shear stress instead of to systemic changes in the plasma hormone levels. Our laboratory's previous studies with rat aortic specimens (7,17) have shown that chronic exercise or flow pretreatment of vascular segments increases ACh-induced intracellular calcium elevation in endothelium, which is one of the major upstream signals in endothelium-derived NO production. As the promoter region of eNOS gene contains a shear stress-responsive element (20), exercise training may upregulate eNOS gene expression by an increase in shear stress, and then facilitate NO release.…”
Section: Discussionmentioning
confidence: 99%